Evidence-Based Design in Architectural Education: Designing the First Maggie's Centre in Israel - Pilosof, Nirit Putievsky; Grobman, Yasha Jacob (HERD, 2021)
The study examines the integration of the Evidence-based Design (EBD) approach in healthcare architecture education in the context of an academic design studio. Previous research addressed the gap between scientific research and architectural practice and the lack of research on the use of the EBD approach in architectural education. The research examines an undergraduate architectural studio to design a Maggie's Centre for cancer care in Israel and evaluates the impact of the EBD approach on the design process and design outcomes. The research investigates the impact of the integration of three predesign tasks: (1) literature review of healing architecture research, (2) analysis and comparison of existing Maggie's Centres, and (3) analysis of the context of the design project. The literature review of scientific research supported the conceptual design and development of the projects. The analysis of existing Maggie's centers, which demonstrated the interpretation of the evidence by different architects, developed the students' ability to evaluate EBD in practice critically, and the study of the projects' local context led the students to define the relevance of the evidence to support their vision for the project. The research demonstrates the advantages of practicing EBD at an early stage in healthcare architectural education to enhance awareness of the impact of architectural design on the users' health and well-being and the potential to support creativity and innovative design. More studies in design studios are needed to assess the full impact of integrating EBD in architectural education.